2020
DOI: 10.1371/journal.pone.0228706
|View full text |Cite
|
Sign up to set email alerts
|

Associations between prenatal serum levels of leptin, IGF-I, and estradiol and adolescent mothers’ height gain during and after pregnancy

Abstract: Mexico is within the top three Latin American countries with the highest proportion of adolescent pregnancies while being in the lowest ten Latin American countries in terms of height. It is still unclear how much growth in adolescence is affected by pregnancy; therefore, this study was designed to study the association between prenatal serum concentrations of leptin, IGF-I, and estradiol and the increase in the height of a group of pregnant adolescents between the 28 th week of gestation to one year postpartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although there is much evidence regarding pBMI, GWG, and perinatal outcomes, another strength of our study is that we found that gestational diabetes is also high in pregnant adolescents, which we did not expect. In this sense, timely interventions are needed in this age group because pregnancy impacts the adolescents’ growth [ 4 ] and is probably determining their future metabolic health and their offspring’s. Moreover, teenage mothers usually get pregnant later on, and having had gestational diabetes makes them prone to more maternal and neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is much evidence regarding pBMI, GWG, and perinatal outcomes, another strength of our study is that we found that gestational diabetes is also high in pregnant adolescents, which we did not expect. In this sense, timely interventions are needed in this age group because pregnancy impacts the adolescents’ growth [ 4 ] and is probably determining their future metabolic health and their offspring’s. Moreover, teenage mothers usually get pregnant later on, and having had gestational diabetes makes them prone to more maternal and neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines propose that adolescent pregnant women be categorized using BMI cutoff points for adults and be advised to gain within the same weight gain ranges [ 1 ]. Research has shown that some adolescents may stop or continue their physical growth during pregnancy [ 2 ], depending on their chronological age and energy stores [ 3 , 4 ]; this would also affect their perinatal outcomes [ 5 ]. The IOM recommendations take adolescent growth into account implicitly because lighter adolescents (possibly the younger ones) will most likely be categorized in the lower BMI group, and they would be recommended to gain weight at the highest range [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probably, this is due to a lack of dietary guidelines for pregnant adolescents with different pBMI levels. Health professionals must consider that pregnant adolescent have higher nutrient requirements than adults because adolescents have not yet finished their linear growth [ 4 , 5 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent pregnancy is a high-risk condition associated with a higher probability of adverse maternal and neonatal outcomes, such as delayed intrauterine growth and development and low birth weight [ 2 , 3 ]. Pregnant adolescents are a vulnerable group since their longitudinal growth is compromised [ 4 , 5 , 6 ] and, generally, they consume an excessive or deficient diet in terms of quantity and/or quality [ 7 , 8 , 9 ], in addition to being exposed to adverse psychosocial factors that may influence gestational weight gain [ 10 , 11 ]. As a result, pregnant adolescents worldwide have inappropriate rates of gestational weight gain (GWG).…”
Section: Introductionmentioning
confidence: 99%